Hyperhomocysteinemia Is a Risk Factor of Recurrent Venous Thromboembolism - Eichinger, S.; Stümpflen, A.; Hirschl, M.; Bialonczyk, C.; Herkner, K.; Stain, M.; Schneider, B.; Pabinger, I.; Lechner, K.; Kyrle, P. A. (Thrombosis and Haemostasis, 1998)
Hyperhomocysteinemia is a risk factor of venous thromboembolism. The risk of recurrence in patients with hyperhomocysteinemia is unknown, and the optimal therapy for these patients after acute venous thromboembolism is uncertain.In a multicenter study, 264 patients with an objectively documented single episode of idiopathic venous thromboembolism were prospectively followed after discontinuation of oral anticoagulants. Patients were classified as hyperhomocysteinemic if their homocysteine levels exceeded the 95th percentile of the controls. The outcome events studied were objectively confirmed deep-vein thrombosis and/or pulmonary embolism.Homocysteine levels were elevated in 66 patients (25%) and normal in 198 patients (75%). Recurrent venous thromboembolism occurred in 12 of 66 patients with hyperhomocysteinemia (18.2%) and in 16 of 198 patients without hyperhomocysteinemia (8.1%). The cumulative probability of recurrence 24 months after discontinuation of oral anticoagulants was 19.2 percent (95 percent confidence interval 8.7-27) in patients with hyperhomocysteinemia and was 6.3 percent (95 percent confidence interval 2.4-10.1; p = 0.001) in those without hyperhomocysteinemia. The relative risk of recurrent thrombosis was higher in patients with hyperhomocysteinemia [RR 2.7 (1.3-5.8), p = 0.009].Patients with hyperhomocysteinemia are at high risk of recurrent venous thromboembolism. The high prevalence of hyperhomocysteinemia in thrombosis patients together with the increased risk of recurrence warrants extended patient screening. The impact on the risk of recurrence of prolonged anticoagulation, supplementation of folate and vitamin B12, or both have to be investigated.